Modellgestuẗzte Politikberatung im Naturschutz: Zur "optimalen" Flac̈hennutzung in der Agrarlandschaft des Biosphar̈enreservates "Mittlere Elbe" - Daniel Hillert; Heinz Ahrens; Michael Harth; Thomas Horlitz; Achim Sander (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
– Using the example of the MAB Biosphere Preserve "Mittlere Elbe", this article demonstrates how an "optimal" land-use pattern - a pattern aimed at combining ecological, economic and social objectives in an adequate way - can be determined. The focus is on the definition of alternative nature conservation approaches, the scenario technique, the definition of landscape functions, the utility analysis and the adaptive conjoint analysis. In addition, the authors demonstrate which quantitative methods can be used to obtain the information needed for utility and conjoint analyses on the ecological and economic effects of the conservation scenarios as well as on the weighting of the landscape functions, and how they can be integrated. Finally, it is shown that the conflict between ecological and economic objectives cannot only be reduced by a regional differentiation of the extent of resource protection - as shown in the literature -, but also by a spatial variation of the type of environment conservation.
Keywords: 330; Agrarboden; Naturschutzgebiet; Scoring-Modell; Conjoint-Analyse; Politikberatung; Politikberatung; Elbe